Analysis of Factors Related to Outpatient Revisit at Waled Regional General Hospital, Cirebon Regency - Nisa Soffiyani; Ayun Sriatmi; Septo Pawelas Arso (International Journal Labs, 2026)
Marketing strategy is important in marketing management. Hospitals need to develop effective strategies to increase outpatient service visits. This study aims to analyze the relationship between the Segmenting, Targeting, and Positioning (STP) strategy with outpatient revisits at Waled Hospital, Cirebon Regency. The design used was quantitative descriptive with a cross-sectional approach in 110 patients (Slovin, 10% error tolerance) who were selected by consecutive sampling. Primary data were collected using a Likert scale questionnaire that was tested for validity (p<0.05) and reliability (?>0.60). The analysis included univariate for perception and bivariate using Chi-Square test (?=0.05) and Spearman Rank test (?=0.05). The results of the respondent's characteristic test showed that it was not related to the outpatient revisit of Waled Hospital. The results showed positive perceptions of segmenting (easy access, services for all ages, easy flow) and positioning (quality is considered good, many polyclinics, affordable prices), while targeting was relatively weak (innovation and promotion are less attractive; routine treatment is low). Although the proportion of repeat visits was higher in the